Ghosts of weather past? Impact of past and present weather-related factors on the seasonal questing activity of Ixodes ricinus nymphs in southwestern Finland - Tanski, Niko; Hänninen, Jari; Kalliola, Risto; Sormunen, Jani Jukka (Springer Science and Business Media LLC, 2025)
Background
Hard ticks are responsible for spreading several zoonotic infections globally. Of the main vector species in Europe, Ixodes ricinus, nymphal ticks cause the largest number of disease cases. Therefore, understanding the seasonal questing behaviour of this life stage is particularly crucial for public health. We assessed seasonal variation in questing abundance of I. ricinus nymphs on a tick-infested island in southwestern Finland. Our primary goal was to examine which abiotic factors, such as meteorological conditions from the recent past, influence the seasonal questing activity of I. ricinus nymphs, and whether these influences manifest similarly across different times and habitat types.
Methods
Ticks were collected in 2012–2021 by cloth dragging from five different biotopes around the island. Three 50-m study transects were placed in each biotope, for a total of 15 transects. Air temperature and relative humidity were measured at the moment of sampling. Daily temperature and rainfall readings were obtained from weather stations.
Results
Across all biotopes, the overall density of I. ricinus nymphs was 10.6 ticks/100 m2. In total, 7082 nymphs were collected from a total sampled area of 67,500 m2. Increasing nymph densities were observed during the 10-year study period, but the increase was not linear. Instead, an incremental jump in densities was observed in 2016. One weather-related explanatory factor remained in each of the statistical models for modelling the seasonal questing activity of ticks, when the progress of the season was already taken into account by week numbers.
Conclusions
Increasing nymph densities were observed during a 10-year study period. While temperature measurements taken during the time of dragging did not appear to greatly influence the observed tick numbers, the recent past temperature variables were significant in all the natural biotopes. The results suggest that, in the clearly seasonal climate of southwestern Finland, the main factors shaping phenological patterns of I. ricinus nymphs during their main activity period are the progress of the season and a heat-related reduction in questing activity.